Operum divi Cyrilli Alexandrini Episcopi tomi quatuor : quorum postremus nunc recens accedit, ex graecis manuscriptis exemplaribus fideliter latinitate donatus . - Cyril, Saint, Patriarch of Alexandria, ca. 370-444 (German books before 1601. Series II, 1546)
Partial contents: I. Commentary on the Gospel of John. On Leviticus. -- 2. Against heretics, on the consubstantiality of the Son and the Holy Spirit, with the Father; on the Trinity, with an appendix: the Holy Spirit is God. -- 3. Apology for Christianity, against Julian the Apostate; on correct faith in Christ. -- 4. Letters; homilies; apology to Theodosium; other apologetical works; exposition of the Nicene Creed; on the incarnation; synodal letters; Nestorianism.